Does interdependency affect firm and industry profitability? an empirical test - Lenox, Michael; Rockart, Scott; Lewin, Arie Y. (Strategic Management Journal, 2009)
Abstract Strategy researchers have argued that heterogeneity in firms' practices and profitability within and across industries may derive from industry‐level differences in the extent of interdependencies among firms' activities. Theoretical models have clarified how and why differences in the extent of the interdependencies faced by firms across industries may affect the distributions of firm profits, but the specific predictions from these models have not been empirically tested. In this paper, we present what we believe is the first large scale empirical analysis linking differences in the extent of interdependencies across industries to differences in the distribution of firm profits within and across those industries. We use survey data to measure interdependencies systematically across a wide number of industries, thus addressing the primary obstacle to incorporating interdependencies in larger scale empirical work, and find evidence consistent with the theoretical predictions: average profitability is highest in industries with moderate levels of interdependency; the dispersion of profits among firms is higher in industries with more extensive interdependencies; and industries with more extensive interdependencies have a more positively skewed performance distribution. We find that the effect of interdependencies on average industry profitability is similar in scale to the effect of patent protection and industry growth rates, placing interdependency squarely among the strategy field's central concepts. Copyright © 2009 John Wiley & Sons, Ltd.